2019
DOI: 10.1021/acs.orglett.9b02498
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Catalyzed Formal [5 + 2] Cycloadditions of Alkylidene β-Ketoesters with Olefins: Chemodivergent Synthesis of Highly Functionalized Cyclohepta[b]indole Derivatives

Abstract: The calcium-catalyzed, formal [5 + 2] cycloaddition of indolyl alkylidene β-ketoesters with mono- and disubstituted aryl olefins to form cyclohepta­[b]­indole derivatives has been established. Unanticipated chemodivergence with phenyl vinyl sulfide/ether revealed a double [5 + 2] cycloaddition cascade providing ethano-bridged cyclohepta­[b]­indoles. Overall, the method’s highlights include: (1) use of a green, calcium-based catalyst (2.5 mol % loading); (2) reaction times under 1 h; (3) mild reaction condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 41 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…As an alternative approach to obtain indole-2-acetic acid with a protecting group at the indole nitrogen the application of conditions documented for Arndt-Eistert synthesis [31] was prompted from benzyl-protected indole-2-carboxylic acid 20 (Scheme 4) [32]. While the acid chloride of unsubstituted indole-2-carboxylic acid was reported to be highly unstable [33], we did not experience that issue with the benzyl-protected compound.…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative approach to obtain indole-2-acetic acid with a protecting group at the indole nitrogen the application of conditions documented for Arndt-Eistert synthesis [31] was prompted from benzyl-protected indole-2-carboxylic acid 20 (Scheme 4) [32]. While the acid chloride of unsubstituted indole-2-carboxylic acid was reported to be highly unstable [33], we did not experience that issue with the benzyl-protected compound.…”
Section: Resultsmentioning
confidence: 99%
“…B. Synthesis of Indolyl-α-diazo-β-ketoesters 1 . General Procedure: Using the following modified literature procedure [ 55 ]: To a dry flask charged with a stir bar and the corresponding indole carboxylic acid (1.0 equiv. ), dry CH 2 Cl 2 was added to make a 0.5 M solution, followed by addition of catalytic DMF (a few drops).…”
Section: Methodsmentioning
confidence: 99%
“…Intriguingly, the racemic bicyclo[3.2.2]nonane‐derived cyclohepta[ b ]indole 79 was obtained by two consecutive non‐concerted (5+2) cycloadditions of 76 with phenyl vinyl thioether 77 (Figure 26). [36] The core carbon structure of the bicyclo[3.2.2]nonane‐derived cyclohepta[ b ]indole 79 resembles the core carbon structure of astolarsine 20 (Figure 5).…”
Section: Cyclohepta[b]indoles From Indolesmentioning
confidence: 95%
“…In 2019, France et al reported the synthesis of racemic tetrahydrocyclohepta[b]indoles 78 by intermolecular (5 + 2) cycloaddition (Figure 25). [36] The catalytically active species is formed in situ from calcium triflimide and tetrabutylammonium hexafluorophosphate. Notably, triflimide (HNTf 2 ) catalyzed the formation of 78 b in 64 % yield.…”
Section: (5 + 2) Cycloadditionsmentioning
confidence: 99%